Revisiting Planning standards of Community Facilities for Urban Areas in Bangladesh - Khan, Adil Mohammed (Journal of Bangladesh Institute of Planners, 2020)
Community facilities are significant components in city planning that are deemed important for sustainable living in cities and settlements. Formulation of appropriate planning standards is necessary while preparing physical plans for urban areas in order to ensure proper community facilities across all parts of the urban areas of a city. This paper revisits planning standards for community facilities as practiced in physical plans and master plans of different metropolitan cities and municipalities in Bangladesh. This study finds that there are deficiencies of community facilities of different types according to the standards, both at metropolitan cities and municipalities in Bangladesh. It reveals that some community facilities are adequate in number as per the planning standards, while they are greatly deficient as per the area standards. Based on the findings of this study, planning standards for various types of community facilities are suggested which could be helpful for formulating future policies and physical plans for urban areas in Bangladesh. However, community facility standards that are recommended in this paper should not be seen as rigid standards by the development agencies or local government authorities. Rather, these set of standards are indicative and therefore can act as a guideline or starting point for assessment of community facilities in the urban areas of Bangladesh. JBIP, Vol. 13, 2020 (Printed in June 2021), pp. 47-68